Faktor-Faktor yang Mempengaruhi Keputusan Dunia Industri dalam Melisensi Teknologi - Nila Sauri Pratesti; Rizal Syarief; Mochammad Mukti Ali (Jurnal Manajemen dan Organisasi, 2022)
The Era of globalization requires every country to always improve their technology in order to provide competitiveness products. One of the factors to increase the country’s competitiveness index is by adopting technology by industry through product licence. Indonesian Agency for Agricultural Research and Development (IAARD) is one of the national R&D institutions that have a role to invent a product for society (non commercial) and industry (commercial through product licence). In the past five years (2015-2019), the total of license between IAARD and the industry slowly decreasing. This study aimed to find out industry’s perceived of IAARD’s technology and factors influenced the industrial decision to license IAARD technology. This research was involving 80 respondents from 57 industries as a license partner (2015-2019). Data analysis technique used was top two boxes for descriptive anaylisis and SEMPLS using SmartPLS version 3.0. The result showed that product innovation and perceived risk have a significant effect on industrial decision to license. Product quality and promotion have no significant effect on industrial decision to license.